Esophageal squamous cell carcinoma complicated with varices successfully treated by endoscopic injection sclerotherapy and argon plasma coagulation: A case report - Sayuri Watanabe; Takuto Hikichi; Takumi Yanagita; Jun Nakamura; Minami Hashimoto; Tsunetaka Kato; Ryoichiro Kobashi; Yuichi Waragai; Masao Kobayakawa; Hiromasa Ohira (DEN Open)
Abstract Treatment guidelines for esophageal squamous cell carcinoma (ESCC) with concomitant esophageal varices (EVs), which increase the risk of bleeding, are unavailable. A 66‐year‐old man with a history of total gastrectomy was admitted to the hospital owing to hematemesis. Emergency upper gastrointestinal endoscopy revealed variceal bleeding near the anastomosis between the esophagus and jejunum, and endoscopic clipping stopped the bleeding. Upper gastrointestinal endoscopy following hemostasis revealed four EVs and a two‐thirds ESCC circumference. The ESCC depth was suspected to be up to the mucosa. The patient underwent intravariceal endoscopic injection sclerotherapy (EIS) for EVs, followed by paravariceal EIS. However, after these treatments, blood flow in the EVs just below the ESCC remained, and endoscopic resection of the ESCC was judged to be difficult to perform. Therefore, we prioritized EV treatment and performed a second EIS on the ESCC, followed by argon plasma coagulation (APC). APC was expected to not only solidify the EVs but also eliminate the ESCC existing in the mucosa. Finally, EVs and ESCC were treated by EIS and APC. EIS followed by APC may be useful for treating concurrent EVs and intramucosal ESCC in patients with liver cirrhosis when embolization of the EVs is ineffective.